Textbook for fundamental information technology engineers : no. 3 : internal design and programming. (Tokyo, Japan : Information-Technology Promotion Agency, Japan, 2006)
V. 1 : Introduction to computer systems, v. 2 : System development and operations, v. 3 : Internal design and programming, v. 4 : Network and database technologies, v. 5 : Current IT topics.
1. Data structures -- 2. Algorithms -- 3. Internal design -- 4. Program design -- 5. Program implementation
Includes index.
Keywords: INFORMATION TECHNOLOGY -- STUDY AND TEACHING